The Domain of Pitch in Music - RAKOWSKI, Andrzej (Archives of Acoustics, 2009)
The aim of this paper is to discuss some of the physical and psycho-physiological mechanisms that contribute to transformation of the unidimensional sensation pitch into the important medium where most significant elements of music-communication code could develop. It is argued that pitch in music should not be regarded as a simple, unidimensional sensation, but it should be seen as a complex auditory system (PITCH DOMAIN) of four sensations, two in the subdomain of PITCH VALUE (natural pitch and categorized pitch or a system of pitch classes) and two in the subdomain PITCH DISTANCE (natural pitch distance and a system of musical intervals). In such a multidimensional structure pitch is particularly suited to overcoming the limitations of memory. Another part of analysis concerns the role of short-term memory (STM) and long-term memory (LTM) operating in relation with various forms of pitch. In particular, an important role of STM for natural pitch is emphasized, in maintaining the stability and coherence of any musical performance. In the remaining parts of this paper the analysis concerns specific forms of the auditory memory that contribute to the sensation of pitch distance, and problems of psychological scaling of pitch.